ANALISIS PENGARUH HARGA, TATA LETAK, KENYAMANAN BELANJA, KELENGKAPAN PRODUK, LOKASI DAN PELAYANAN TERHADAP SIKAP KONSUMEN DENGAN PENDEKATAN REGRESI LINIER BERGANDA - Misbach Munir; Ayik Pusakaningwati (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
In line with the times, there are many trading companies that are engaged in retail trading, such as: shops, minimarkets, supermarkets and others. In Sengonagung department stores, it is known that the purchasing power of consumers is quite high, even though the price offered is the same as other supermarkets. This can be seen from the number of buyers so that it can make a good marketing target. From the large number of buyers who came, it was concluded that there were several attribute factors that influenced consumer purchasing power. The method used is multiple regression which is used to calculate the influence / prediction of two or more variables X on one variable Y. The research was conducted at the Sengonagung Department Store which is located in Sengonagung Village, Kec. Purwosari Kab. Pasuruan. The results of the analysis F count is 12.363, while the results of the F table in the distribution table with an error rate of 5% is 2.27. This means that F count> F table (12.363> 2.27) indicates H1 is accepted and has a positive effect. And the most influential value or H2 is accepted, namely the price variable (X1) which produces a T count value greater than T table, T count (3,732)> T table (1,672), shopping convenience (X3) which results in a T count value greater than T table,Tcount(5,334)>Ttable(1,672).